1H NMR and X-ray Diffraction Investigations of the Complex of S4N3Cl with HgCl - Singh Yadav, Surender; Singh Jadon, S.P. (Asian Journal of Chemistry, 2012)
On the basis of 1H NMR and X-ray diffractometric studies, the complex of S4N3Cl with HgCI, formulated as (S4N3ClHgCl)2 is found to be a bidentate coordinated complex with a triclinic geometrical structure.